2013
DOI: 10.1136/emermed-2012-202326
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CPR outcome predictors between rhythmic abdominal compression and continuous chest compression CPR techniques

Abstract: Although OAC-CPR appeared superior to CC-CPR by pressure and ventilation metrics, lower carotid flow and longer delay until ROSC raise concerns about overall performance. These paradoxical observations suggest that the evaluation of efficacious alternative CPR techniques may require more direct measurements of vital organ perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 42 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…108,109 However, its role in patients after cardiac surgery has been questioned, 110 and recent studies have not found it to be as effective as closed chest massage for cardiopulmonary resuscitation (CPR) in other circumstances. 111,112 Thus, my recommendations (which are the personal opinion of this author and not evidence based) for management of cardiac arrest in a patient with a VAD are the following:…”
Section: Arrhythmia Management and Cardiac Arrest In Patients With Lvadsmentioning
confidence: 99%
“…108,109 However, its role in patients after cardiac surgery has been questioned, 110 and recent studies have not found it to be as effective as closed chest massage for cardiopulmonary resuscitation (CPR) in other circumstances. 111,112 Thus, my recommendations (which are the personal opinion of this author and not evidence based) for management of cardiac arrest in a patient with a VAD are the following:…”
Section: Arrhythmia Management and Cardiac Arrest In Patients With Lvadsmentioning
confidence: 99%
“…Complete recoil cannot be achieved when performing effective-depth chest compressions at a 100/min rate, 50-mm compression depth and 50% duty cycle (or without high-impulse CPR) [9]. But, evidence suggests that very few rescuers can perform effective CPR despite receiving high quality basic life support training and/or while using feedback technology [10][11][12][13][14] likely because the typical rescuer (bystander or professional) lacks a combination of adequate height and upper-body weight [15,16].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…However, the generation of substantial compression-induced ventilation requires that the compression depth not only has to be deep enough to displace adequately more air out of the lungs than dead space, but also, recoil time has to be long enough to allow the lung to refill with the amount of air displaced. A 38-mm compression depth is not deep enough to displace enough air from the lungs such that it is greater than the dead space [9];…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies of alternative CPR techniques require evaluation of the resulting perfusion of vessels supplying the heart, brain, and other vital organs. [ 1 ] Hand-only CPR is recommended in OHCA, especially in adults, because several important studies found that layperson hand-only CPR was associated with better survival after OHCA compared to conventional CPR. [ 2 3 4 ]…”
Section: Ompression and V Entilation mentioning
confidence: 99%